NADES EXTRACT OF GEDONG MANGO LEAVES AND MULBERRY LEAVES IN SPRAY GEL AS A SUNSCREEN - RIZIKIYAN, YAYAN; SUHARYANI, INE; FALYA, YUNIARTI; AMELIA, RENNY; NUH, MUHAMMAD; SULASTRI, LELA; INDAWATI, IIN (International Journal of Applied Pharmaceutics, 2022)
Objective: This study's purpose was to formulate a spray gel containing the combination extract of gedong mango leaves and mulberry leaves as a sunscreen preparation. Methods: Each leaf was extracted by Natural Deep Eutectic Solvent-Maceration Assisted Extraction (NADES-MAE) method. The extract (gedong mango and mulberry leaves) formulated in Carbopol Spray Gel/GM-CarSG) in a ratio of GL and ML were 3:0.5 (GM-CarSG 1); 3:3 (GM-CarSG 2); and 3:6 (GM-CarSG 3). Furthermore, the spray gel was evaluated, and the SPF value was determined. Results: The physical appearance, spreadability, pH, and viscosity of GM-CarSG 1, GM-CarSG 2, and GM-CarSG 3 meet the requirements. In addition, the three preparation have a sunscreen activity, with the SPF value of GM-CarSG 1, GM-CarSG 2, and GM-CarSG 3 being 2.08+0.03; 2.78+0.05; and 3.53+0.04, respectively. Conclusion: The results showed that the combination of GL and ML extract is potentially used as a sunscreen in spray gel preparation. The best formulation is GM-CarSG 3, which has the highest SPF value among them.